The Fiqh Wasaṭiyyah Approach Towards the Involvement of Malaysian Women in Religious Extremism Phenomenon - Abd Razak, Muhd Imran; Ramli, Mohd Anuar; Abdul Rahim, Rahimin Affandi; Awang Pawi, Awang Azman; Yusof, Muhammad Yusri; Hassan, Paiz (Al-Risalah, 2019)
The trend of women’s active participation in religious extremism phenomenon has become a serious global threat, including for Southeast Asian countries such as Indonesia and Malaysia. This paper aims to offer a fiqh approach in the form of wasaṭiyyah in order to reinforce counter-laws of religious extremism, especially on the issue of Malaysian women’s involvement in the Daesh extremist group (al-Dawlah al-Islāmiyyah fī al-ʻIrāq wa al-Shām). Through library and field research, this paper concludes that an approach of fiqh wasaṭiyyah, which is based on the reality of law and the reality of religious extremism, can be developed. This research is hoped to assist various parties, especially the Malaysian government, to improve existing deradicalization process and strengthen the efforts to restraint religious extremism in the grassroots.